Population-based incidence and antimicrobial susceptibility patterns of shigellosis among children and adults from rural and urban Kenya, 2010–2019 - Richard Omore; Billy Ogwel; John B. Ochieng; Jane Juma; Victor Omballa; Alice Ouma; George Aol; Allan Audi; George O. Agogo; George Odongo; Clayton Onyango; Newton Wamola; et al. (PLoS ONE, 2026)
Backgroun Shigella is an important cause of diarrheal morbidity and mortality globally. Data on disease burden across age groups, in different epidemiologic settings, and over time are needed to guide preventive strategies. We examined shigellosis in two sites in Kenya over a 10-year period. Methods We used data from the Population-Based Infectious Disease Surveillance (PBIDS) platform in a rural (Asembo, population ~35,000) and urban (Kibera, population ~23,000) setting. PBIDS participants presenting to surveillance clinics with diarrhea (≥3 loose stools in 24-hour period) had stool collected and cultured; Shigella isolates underwent antimicrobial susceptibility testing. We estimated incidence by dividing Shigella cases by person-years- observation, adjusting for the proportion of diarrhea cases with stool collected and for care-seeking outside surveillance clinics. Results From January 1, 2010 to December 31, 2019, we isolated Shigella from 23% and 15% of 2,017 and 4,074 stool specimens collected in Asembo and Kibera, respectively; S. flexneri accounted for 61% and 67%, respectively. In Asembo, the adjusted shigellosis incidence was 684/100,000; it was highest in ages 12–23 months (1,873/100,000) and ≥50 years (1,502/100,000). In Kibera, the adjusted incidence was 647/100,000, highest in ages 12–23 (2,828/100,000) and 24–59 months (936/100,000). Incidence declined significantly in Asembo (p = 0.009), but not in Kibera (p = 0.53). Overall, ≥ 97% of isolates were susceptible to ciprofloxacin and ceftriaxone. Conclusion The shigellosis burden was greatest among young toddlers in both urban and rural areas and was high among older adults in the rural setting. Although resistance to first-line antibiotics was infrequent, continued susceptibility monitoring is warranted.